2014
DOI: 10.1186/s12955-014-0108-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative patient characteristics on health states after total hip replacement and related satisfaction thresholds: a cohort study

Abstract: BackgroundThe aim of the study was to analyze the effect of preoperative patient characteristics on health outcomes 6 months after total hip replacement (THR), to support patient’s decision making in daily practice with predicted health states and satisfaction thresholds. By giving incremental effects for different patient subgroups, we support comparative effectiveness research (CER) on osteoarthritis interventions.MethodsIn 2012, 321 patients participated in health state evaluation before and 6 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 34 publications
(65 reference statements)
3
28
0
2
Order By: Relevance
“…A clear dependency of satisfaction and WOMAC scores on the baseline status has been shown before with higher baseline scores yielding in higher PASS cutoffs [41,42]. In another investigation including 321 THA patients with baseline WOMAC scores comparable to those in the present study (i.e., 52 points), the PASS threshold at 6 months has been indicated with 85 points [43], matching the value we found at the same time point. Somewhat surprisingly, no effect of baseline scores on PASS thresholds at 1 year after THA was found by Paulsen et al [44] for the HOOS and EQ-5D, but these authors indicated gender and age effects.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A clear dependency of satisfaction and WOMAC scores on the baseline status has been shown before with higher baseline scores yielding in higher PASS cutoffs [41,42]. In another investigation including 321 THA patients with baseline WOMAC scores comparable to those in the present study (i.e., 52 points), the PASS threshold at 6 months has been indicated with 85 points [43], matching the value we found at the same time point. Somewhat surprisingly, no effect of baseline scores on PASS thresholds at 1 year after THA was found by Paulsen et al [44] for the HOOS and EQ-5D, but these authors indicated gender and age effects.…”
Section: Discussionsupporting
confidence: 88%
“…They reported a 1-year PASS of 0.92 for the EQ-5D index [44], the similar value we found in the present investigation. Vogl and associates indicated a 6-month PASS for the EQ-5D VAS of 79 that is well transferrable to the value 0.76 we found for the EQ-5D index at 6 months since both subscales are highly correlated with each other [43]. It seems therefore that different PROMs are more prone to be dependent on the preoperative patient status than others.…”
Section: Discussionsupporting
confidence: 76%
“…Várias informações fundamentais relacionadas ao período pré-operatório não foram citadas pelos indivíduos pesquisados, tais como: informações sobre tipo e tempo de manutenção da prótese; risco da cirurgia e possíveis complicações; restrições e limitações relacionadas à cirurgia; consentimento para a cirurgia; problemas e intervenções relacionados com ansiedade, medo, distúrbios do sono; estímulo ao autocuidado dentro das limitações do paciente; cuidados gerais de Enfermagem e de prevenção da síndrome do desuso; medicamentos específicos para problemas identificados e alterações de esquemas terapêuticos cotidianos; realização de exames laboratoriais e por imagem; avaliação pré-operatória pelo enfermeiro do Centro Cirúrgico (6,(13)(14)(15)(16)(17)(18)(19)(20) .…”
Section: Discussionunclassified
“…Além desses, também foram omitidos: riscos relacionados à anestesia; informações sobre o protocolo de cirurgia segura; necessidade de suporte social; cuidados e restrições durante a recuperação pós-anestésica e após o retorno à unidade de internação; limitações no pós-operatório hospitalar e após a alta; cuidados após a alta; adaptações e modificações da residência; presença e controle da dor pré e pós-operatória; necessidade de transfusão de sangue; evolução e tratamento das comorbidades; necessidade de ser encaminhado à Unidade de Terapia Intensiva no pós-operatório; e, medicamentos pré-anestésicos e encaminhamento ao Centro Cirúrgico (6,(13)(14)(15)(16)(17)(18)(19)(20) .…”
Section: Discussionunclassified
“…12,13 However, patients with severely affected states of health generally do not reach the levels of health achieved in those with less severe symptoms before surgery. 12,13 Furthermore, the bounded nature of instruments often limits their ability to discriminate between good and excellent outcomes. Consequently, when evaluating outcomes from the patients' perspective, one has to consider the change as well as the absolute level of pain, function and healthrelated quality of life.…”
Section: Improvement or Absolute Level Of Function Pain And Health mentioning
confidence: 99%